2013
DOI: 10.1111/j.1468-2338.2012.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Working hours in Chinese enterprises: evidence from matched employer–employee data

Abstract: The purpose of this article is to explore the factors that are correlated with hours worked in China. A distinguishing feature of the study is that we used representative‐matched employer and employee data. Hence, in addition to the usual worker characteristics examined in conventional economic models of labour supply, we also took into account the influence of firm characteristics and policies on the number of hours worked. The results suggested that in addition to the hourly wage rate, labour supply characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
2
15
0
1
Order By: Relevance
“…The signs on the coefficients of most of the other variables are consistent with previous studies of the determinants of labour supply in China (see eg. Li & Zax, 2003;Mishra & Smyth, 2013;Smyth, Qian, Nielsen & Kaempfer, 2013). Of note, the coefficient on monthly wages is negative and statistically significant for migrant workers, which suggests the existence of a backward bending labour supply curve.…”
Section: Resultsmentioning
confidence: 92%
“…The signs on the coefficients of most of the other variables are consistent with previous studies of the determinants of labour supply in China (see eg. Li & Zax, 2003;Mishra & Smyth, 2013;Smyth, Qian, Nielsen & Kaempfer, 2013). Of note, the coefficient on monthly wages is negative and statistically significant for migrant workers, which suggests the existence of a backward bending labour supply curve.…”
Section: Resultsmentioning
confidence: 92%
“…The incidence of overtime work is prevalent, especially in the manufacturing and commercial service sectors (Verité 2004(Verité , 2012Ye, Gindling, and Li 2015). Using an employer-employee matched dataset in Shanghai, Vinod Mishra and Russell Smyth (2013) found that employees worked longer hours in firms that employed a high proportion of women and migrant workers. They also found that workers who received lower pay worked longer hours.…”
Section: Working Time Regulationsmentioning
confidence: 99%
“…Of particular interest to our study is the research on work hours and health in Japan and South Korea, both of which have long work weeks like China (Mishra & Smyth, 2013).…”
Section: Long Work Hours and Subjective Healthmentioning
confidence: 99%
“…China's long weekly work hours, among the longest in the world, have given rise to substantial concerns about the negative effects such a work week may have on workers' health (Mishra & Smyth, 2013). In a recent survey of Chinese workers, for example, respondents pointed to long work hours as one of three major reasons for health problems (Tang, 2013).…”
Section: Introductionmentioning
confidence: 99%